Negative campaigns in X (formerly known as Twitter) for the 2021 presidential campaigns in Chile - Soto Pincheira, Daniel (Re-presentaciones: Periodismo, comunicación y sociedad, 2025)
The aim of this article is to understand how negative campaigning worked during the 2021 presidential campaigns on social media X (formerly known as Twitter). This mixed-methods research integrated quantitative and qualitative approaches to analyze the accounts of the seven presidential candidates who ran for office and determine the extent to which this tactic was employed in the campaign. The findings show that negative campaigning is present on X, with José Antonio Kast (Republican Party) being the candidate who used this strategy the most. Furthermore, the study helps identify that candidates who faced less negative campaigns, ranked lowest in the elections, whereas those attacked the most, secured the first positions. That is the case of Gabriel Boric, who was ultimately elected president.